Antioxidant defenses at transcriptional and enzymatic levels and gene expression of Nrf2-Keap1 signaling molecules in response to acute zinc exposure in the spleen of the large yellow croaker Pseudosciaena crocea. (May 2016) - Zheng, Jia-Lang; Zeng, Lin; Shen, Bin; Xu, Mei-Ying; Zhu, Ai-Yi; Wu, Chang-Wen
Abstract: We evaluated the effects of acute Zn exposure (4 and 8 mg L −1 Zn) on lipid peroxidation, and activities and mRNA levels of antioxidant enzyme genes (Cu/Zn-SOD, CAT, GPx, and GR), and gene expression of the Nrf2-Keap1 signaling molecule at different exposure times (0, 6, 12, 24, 48, and 96 h) in the spleen of large yellow croaker. Lipid peroxidation remained relatively constant during 6–48 h and 6–24 h and sharply increased at 96 h and during 48–96 h in fish exposed to 4 and 8 mg L −1 Zn, respectively. Activities of all tested enzymes increased during the early stage of exposure and decreased towards the end of the exposure in both groups. However, mRNA levels of antioxidant enzyme genes were dramatically up-regulated by 4 and 8 mg L −1 Zn during the late stage of exposure. During the early stage of exposure for 6 h, the 8 mg L −1 Zn exposure sharply increased mRNA levels of Cu/Zn-SOD, CAT, GPx1b, Nrf2, and Keap1, whereas, the 4 mg L −1 Zn exposure did not significantly affect the expression of these genes. Our data also showed positive relationships between Nrf2 expression and mRNA levels of its target genes, suggesting that Nrf2 was required for the protracted induction of these genes. Furthermore, a sharp increase in Keap1 expression levels was observed in fish exposed to 4 mg L −1 at 96 h, and 8 mg L −1 at 6, 48, and 96 h. In conclusion, the present study demonstrated that Zn-induced antioxidant defenses were involved in modifications at enzymatic and transcriptional levels and the transcriptional regulation of the Nrf2-Keap1 signaling molecule; these results may contribute to the understanding of mechanisms that maintain the correct redox balance in the immune organ of the large yellow croaker. Highlights: Fish spleen showed a capacity of detoxification against Zn stress. This capacity depended on the regulation at enzymatic and transcriptional levels. Transcription factor Nrf2 played a central role in antioxidant defenses.